2013
DOI: 10.1002/cbdv.201200165
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil of Indian Propolis: Chemical Composition and Repellency against the Honeybee Apis florea

Abstract: Hitherto unknown biological properties and the chemical composition of the essential oil isolated from propolis of Indian origin were established. GC/MS Analysis of the essential oil revealed the presence of 32 constituents, of which ten were major compounds, nine had intermediate contents, and 13 were minor compounds. With the exception of six minor constituents, that could not be identified, their identification was based on the comparison of their mass spectra and Kovats retention indices with those listed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 28 publications
1
15
1
Order By: Relevance
“…1-docosene, hexadecane, octacosane, hexacosene and heptacosane identified in Nafplio sample, are also reported for the first time in Greek propolis. Octacosane was reported as a constituent of Dubai propolis [42], while heptacosane and related compounds have been reported in the essential oil of Indian propolis [43]. Episesamin is a furofuran lignan that was reported by Bankova et al, in Canary Islands propolis [44].…”
Section: Resultsmentioning
confidence: 99%
“…1-docosene, hexadecane, octacosane, hexacosene and heptacosane identified in Nafplio sample, are also reported for the first time in Greek propolis. Octacosane was reported as a constituent of Dubai propolis [42], while heptacosane and related compounds have been reported in the essential oil of Indian propolis [43]. Episesamin is a furofuran lignan that was reported by Bankova et al, in Canary Islands propolis [44].…”
Section: Resultsmentioning
confidence: 99%
“…However, this is in agreement with the repellent activity observed for other essential oils. Essential oils from leaves of S. densifolia (Naik et al 2008), fruits of Terminalia chebula (Naik et al 2010b), and Indian propolis (Naik et al 2013) have previously been reported as repellent to honey bees. In a continuation of this line of research, here we report the isolation of components of the essential oil of flowers of S. densifolia and characterization of their repellent properties.…”
Section: Discussionmentioning
confidence: 99%
“…A natural colony of Indian honey bees A. florea nested in open space on the campus of Agharkar Research Institute was used for bioassays. Bioassays of each of the test formulation were carried out using a rotating table bioassay (Naik et al 2013), in which a table with a rotating circular wooden top (60 cm in diameter) mounted on an electric motor was fitted with a removable glass top of the same diameter. Throughout the experiment, the table top was 25 cm above the ground and was rotated at a constant velocity of one rotation every three minutes.…”
Section: Methodsmentioning
confidence: 99%
“…KP EO is quite different in comparison with KP HS containing higher alkanes as the major constituents: heneicosane (4.1%), docosane (13.5%), tricosane (31.8%) and tetracosane (25.4%). Indian propolis EO contained [35] among major constituents long-chain alkanes (tricosane (13.6%), hexacosane, heptacosane and heneicosane). Two sesquiterpene alcohols were found as major compounds in KP EO: guaiol (3.1%) and manool (5.7%).…”
Section: Nomentioning
confidence: 99%
“…Higher alkanes were also present: heneicosane (1.0%), docosane (11.2%), tricosane (5.2%) and tetracosane (9.4%). EO of Indian propolis [35] was shown to contain 45.83% of long-chain alkanes (including heneicosane, tricosane, hexacosane and heptacosane).…”
Section: Mediterranean Propolis (Poplar Type) Volatilesmentioning
confidence: 99%